Features Of Pre-Pregnancy Preparation of Women with a History Of Miscarriage. - Alimova H. A; Karimova N.N. (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Infectious diseases, especially opportunistic infections, have become a major concern in obstetrics due to their association with immunodeficiency and severe perinatal complications. Specific background: TORCH infections, including herpes simplex virus, cytomegalovirus, chlamydia, and toxoplasmosis, are known to contribute to spontaneous miscarriages, fetal malformations, and intrauterine mortality. Knowledge gap: Despite the availability of antiviral and antibacterial therapies, evidence regarding the effectiveness of immunomodulatory agents such as Proteflazid in improving reproductive outcomes in women with recurrent miscarriage remains limited. Aims: This study aimed to evaluate the therapeutic efficacy of Proteflazid in the complex treatment of women with TORCH infections. Results: Among 30 women aged 20–33 years, Proteflazid administration led to significant clinical improvement, with 80% of patients reporting the disappearance of symptoms and ELISA results showing a 90% reduction in toxoplasma and chlamydia titers and a 78.9% decrease in HSV and CMV titers. Novelty: The study demonstrates the beneficial immunomodulatory and antiviral effects of Proteflazid in enhancing infection control and reproductive health. Implications: These findings suggest that integrating Proteflazid into standard TORCH infection therapy may improve pregnancy outcomes and reduce perinatal morbidity and mortality.Highlight : The study evaluates the effectiveness of Proteflazid in complex therapy for women with TORCH infection. Combination treatment showed significant improvement in clinical and laboratory results. Emphasizes immune system strengthening to prevent miscarriage and fetal deformities. Keywords : Infection, Immunity, Virus, TORCH Infection, ELISA Analysis